Coherent Circulation Changes in the Deep North Atlantic From 16°N and 26°N Transport Arrays. Issue 5 (17th May 2018) - Frajka‐Williams, E.; Lankhorst, M.; Koelling, J.; Send, U.
Abstract: The meridional overturning circulation (MOC) has been measured by boundary arrays in the Atlantic since 2000. Over the past decade of measurements, however, the reported tendencies in overturning circulation strength have differed between 16°N and 26°N. Here we investigate these differences by diagnosing their origin in the observed hydrography, finding that both arrays show deep waters (below 1, 100 dbar) at the western boundary becoming fresher and less dense. The associated change in geopotential thickness is about 0.15 m 2 s −2 between 2004–2009 and 2010–2014, with the shift occurring between 2009 and 2010 and earlier at 26°N than 16°N. In the absence of a similar density change on the east of the Atlantic, this middepth reduction in water density at the west would drive an increase in the shear between the upper and lower layers of North Atlantic Deep Water of about 2.6 Sv at 26°N and 3.9 Sv at 16°N. These transport anomalies result in an intensifying tendency in the MOC estimate at 16°N, but at 26°N, the method of correcting the geostrophic reference level results in an opposing (reducing) tendency of the MOC. The results indicate that both arrays are observing coherent, low‐frequency changes, but that there remain discrepancies in the methods of addressing the geostrophic reference level for boundary arrays measuring ocean circulation. Plain Language Summary: The Atlantic Meridional Overturning Circulation (MOC), sometimes known as the great ocean conveyor, moves heat northwards in the Atlantic in the top 1km of the oceans, with deep water moving southward at depth. Observational programs have been continuously monitoring how quickly this ocean circulation is moving at various latitudes in the Atlantic since the early 2000s. In this paper, we compare measurements of the MOC at 26N and 16N to try to understand how the circulation has been changing during more than a decade of observations. We find that estimates of the overall MOC strength indicate a decreasing circulation strength at 26N, but increasing at 16N. This difference can be traced to choices made during the calculation of the MOC, but that the raw observations at the two latitudes show coherent changes on interannual and longer timescales. Key Points: Coherent hydrographic changes are observed at 16°N and 26°N in western Atlantic At both latitudes, reducing densities below 1, 000 m have resulted in intensified zonal shear since 2009/2010 Opposing decadal trends of the MOC at the two latitudes result from geostrophic reference level choices